Team Building in the Classroom: Preparing Students for Their Organizational Future - Barker, Randolph T. and Franzak, Frank J. (Journal of Technical Writing and Communication, 1997)
Group class exercises have the potential to provide important lessons for students. However, in completing these exercises, business students may not be getting all of the benefits from group work that a team experience could provide. The challenge to business educators is to provide a meaningful team experience within the limitations presented by the class environment. This article describes organizational communication and marketing classes that applied team formation and team-building exercises to enrich the team experience and differentiate it from typical group work.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC91NGI1LTExMWMtdW1lMC02eHh5